Activation of Imidazoline I-2B Receptor by Metformin to Increase Glucose Uptake in Skeletal Muscle - Chen, C.-T; Chen, W.; Chung, H.-H; Cheng, K.-C; Yeh, C.-H; Cheng, J.-T (Hormone and Metabolic Research, 2011)
Metformin (dimethylbiguanide) belongs to guanidinium-derivative and is widely used for treatment of diabetic disorders in clinic. Metformin lowers blood glucose in diabetic animals through increase of glucose uptake into skeletal muscle. Recent evidence indicates that activation of imidazoline I2B receptor (I2BR) by guanidinium-derivatives also increased glucose uptake; however, the effect of metformin on I2BR is still unknown. The blood glucose levels were determined by a glucose kit. The ability of glucose uptake into isolated skeletal muscle or cultured C2C12 cells was determined using 2-[14C]-deoxyglucose as tracer. The expressions of 5′ AMP-activated protein kinase (AMPK) and glucose transporter 4 (GLUT-4) were identified by Western blotting analysis. The metformin-induced blood glucose-lowering action was dose-dependently blocked by BU224, a specific I2R antagonist, in Wistar rats. Also, similar reversion by BU224 was observed in isolated skeletal muscle regarding the metformin-induced glucose uptake. Moreover, AMPK phosphorylation by metformin was concentration-dependently reduced by BU224 in isolated skeletal muscle. In addition, signals for metformin increased glucose uptake were identified via I2R/PI3K/PKC/AMPK dependent pathway in C2C12 cells. Thus, we suggest that metformin can activate I2BR to increase glucose uptake and I2BR will be a new target for diabetic therapy.
Keywords: 5′ AMP-activated protein kinase; BU224; diabetes; glucose transporter 4; metformin